Students Readiness to Do Direct Learning during the Reemerging Covid-19 Pandemic - Krisnandari, Anak Agung Istri Wulan Krisnandari; Rahyanti, Ni Made Sri; Pranata, Gst. Kade Adi Widyas (Jurnal EduHealth, 2022)
Coronavirus Disease 2019 (Covid-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). To anticipate the spread of this virus, government make a regulation that change the learning activity at school from offline to online. However, in mid-May 2021, with the decreasing number of Covid-19 cases, the government began preparing for direct learning activities. The aim of this study was to determine the student readiness to do direct learning. This study used descriptive correlation research using a cross sectional approach. Sampled that have been used in this study were 472 students from one college in Bali. The sampling technique used is total sampling. Data was collected using questionnaire “Learning Readiness Survey Questionnaire during The Covid-19 Pandemic”, that divided into three parts: a). Respondent characteristics, readiness to do direct learning, exposure and Covid-19 vaccine history, and medical history b). Knowledge related to Covid-19, and c). Health behavior during Covid-19 pandemic. Data that has been collected then analyzed using a descriptive test to determine the description of student readiness to do direct learning. The result from this study shows that the majority of students stated that they were ready to do direct learning (89%). Most of them also already got Covid-19 vaccine (98,5%). Majority of the students also have a good understanding regarding Covid-19 (>80%) and implemented Covid -19 prevention behaviour (>90%).